COVID-19 impacts on financial markets: Takeaways from the third wave - Hamza Bouhali (Voprosy Ekonomiki, 2021)
This study provides an updated analysis of the impact of COVID-19 daily contaminations and vaccinations on the financial markets by incorporating the third wave observed in 2021. Our methodology is based on a comparative approach using a multivariate heteroscedasticity model and data from the Eurozone and ten other countries from different economies. Our results show that COVID-19 contaminations and vaccinations strongly affected most of the countries in our sample (except for the UK, Russia and India in the case of COVID-19 contaminations). We also found that optimistic market sentiment concerning the evolution of the pandemic prevailed among the countries forming our sample (except for Switzerland, Russia and India).